3D-printing techno-network to help students overcome mathematical learning difficulties. (19th July 2021) - Mavri, Maria
Three-dimensional (3D) printing is a new manufacturing technology that has many applications related to social, economic, and environmental activities. In this study, we introduce the concept of a 3D printing techno-network, which is a network of humans and the resources they use to engage in a 3D printing procedure. We claim that this network could both influence and improve educational activities to help students with Mathematics Learning Difficulties (MLD) better understand mathematics. The paper proposes an educational scenario of teaching mathematical algorithms using this innovative technology. Mathematical understanding learning outcomes and the adoption of technological achievements are evaluated through a proposed framework consisting of 12 educational and technological indicators.